2013
DOI: 10.1016/j.mrfmmm.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The roles of DNA polymerase ζ and the Y family DNA polymerases in promoting or preventing genome instability

Abstract: Cancer cells display numerous abnormal characteristics which are initiated and maintained by elevated mutation rates and genome instability. Chromosomal DNA is continuously surveyed for the presence of damage or blocked replication forks by the DNA Damage Response (DDR) network. The DDR is complex and includes activation of cell cycle checkpoints, DNA repair, gene transcription, and induction of apoptosis. Duplicating a damaged genome is associated with elevated risks to fork collapse and genome instability. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 244 publications
(221 reference statements)
0
69
0
1
Order By: Relevance
“…19,26,44 Indeed, we found that it did not bypass O 6 -CMG, but readily extended from all primers terminated with canonical bases paired with the adduct. This observation is fully consistent with a predominant function of ζ being to extend after mismatches or TLS.…”
Section: Scheme 2 Synthesis Of ! 6 -Carboxymethylguaninephosphoramiditementioning
confidence: 78%
See 1 more Smart Citation
“…19,26,44 Indeed, we found that it did not bypass O 6 -CMG, but readily extended from all primers terminated with canonical bases paired with the adduct. This observation is fully consistent with a predominant function of ζ being to extend after mismatches or TLS.…”
Section: Scheme 2 Synthesis Of ! 6 -Carboxymethylguaninephosphoramiditementioning
confidence: 78%
“…This observation is fully consistent with a predominant function of ζ being to extend after mismatches or TLS. 19,26,44 It had similar efficiency in extending from the matched, C terminated primer, as well as from the mismatched T-and A-terminated primers paired with O 6 -CMG-containing template.…”
Section: Scheme 2 Synthesis Of ! 6 -Carboxymethylguaninephosphoramiditementioning
confidence: 91%
“…Interestingly, REV7 has several cellular functions including translesion DNA synthesis (TLS) (9,10), mitotic checkpoint regulation (11,12), and DNA repair pathway choice (13,14). Which if any of these functions of REV7 is required for suppressing the FA cellular and developmental phenotypes is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…TLS is a tolerance pathway of replication block caused by DNA lesions (58,59). To measure the e‹cien-cy andˆdelity of TLS in human cells, a new shuttle vector assay system was established recently (60).…”
Section: Prospects For New Shuttle Vector Development To Study Tlsmentioning
confidence: 99%